2016
DOI: 10.1016/j.bbrc.2016.04.100
|View full text |Cite
|
Sign up to set email alerts
|

A negative-feedback loop regulating ERK1/2 activation and mediated by RasGPR2 phosphorylation

Abstract: The dynamic regulation of ERK1 and −2 (ERK1/2) is required for precise signal transduction controlling cell proliferation, differentiation, and survival. However, the underlying mechanisms regulating the activation of ERK1/2 are not completely understood. In this study, we show that phosphorylation of RasGRP2, a guanine nucleotide exchange factor (GEF), inhibits its ability to activate the small GTPase Rap1 that ultimately leads to decreased activation of ERK1/2 in cells. ERK2 phosphorylates RasGRP2 at Ser394 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…This could be explained by the negative regulation of CalDAG-GEFI activity by ERKs, as previously described. 40 All these results support the notion that Shp2 is the phosphatase regulated by ERKs that dephosphorylates and inhibits C3G.…”
Section: Shp2 Colocalizes With C3g and Inhibits Its Gef Activitysupporting
confidence: 72%
See 1 more Smart Citation
“…This could be explained by the negative regulation of CalDAG-GEFI activity by ERKs, as previously described. 40 All these results support the notion that Shp2 is the phosphatase regulated by ERKs that dephosphorylates and inhibits C3G.…”
Section: Shp2 Colocalizes With C3g and Inhibits Its Gef Activitysupporting
confidence: 72%
“…Taken together, these results suggest the existence of a positive regulatory mechanism mediated by ERKs that, through the inhibition of Shp2, enhances the phosphorylation of C3G induced by thrombin. Interestingly, ERKs inhibit CalDAG-GEFI, 40 which raises the idea that ERKs can positively or negatively regulate the activity of Rap1b through the modulation of its GEFs.…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies proposed a role for CalDAG GEFI in ERK1/2 activation [ 10 , 11 , 48 ]. Kawasaki et al found that overexpression of CalDAG GEFI in 293T cells inhibits Elk1 activation and assumed that this would lead to reduced phosphorylation of ERK1/2 further downstream [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of Rap1 nucleotide exchange was measured using a fluorescence-based in vitro enzyme assay 17 , 45 , 46 . 100 µL of reaction buffer (20 mM Tris base, 150 mM NaCl, 5 mM MgCl 2 , 2 mM dithiothreitol, 10% [v/v] glycerol, 0.08% [v/v] NP-40, 1 µM Rap1B, 0.1 µM BODIPY-FL-GDP, pH = 7.5) was aliquoted into wells of a Nunc F96 well, black, flat-bottomed plate and the baseline fluorescence intensity (F.I.)…”
Section: Methodsmentioning
confidence: 99%